Latin saying «pecunia non olet» in the structure of creolized texts - Nina Yurievna, Mikitenko (2021)
The article analyzes a new form of Internet communication - a creolized text consisting of two inhomogeneous parts – visual and verbal. The object of the research is Internet memes, as the most frequent cases of  creolized texts.The Internet meme is a single semantic entity, in which the visual and verbal parts are combined with each other in different ways. Memes, the verbal part of which is represented by the Latin saying "money does not smell" (pecunia non olet), were selected for the analysis. The purpose of the research is to study the parameters of semantic relations between text and images. The attention is drawn to diverse linguistic and creative forms of transformation and reinterpretation of this statement to create the effect of defeated expectancy. Techniques of language play in the texts of the verbal part also contribute to the achievement of a humorous effect.